Senam Tera Menurunkan Tekanan Darah Pada Lansia Penderita Hipertensi Di Kelurahan Sragen Wetan - Alena Fajar Meirawati; Dewi Kartika Sari (Journal of Educational Innovation and Public Health, 2023)
Background; Blood pressure can be said to be normal depending on a person's age and daily activities. Based on data from the World Health Organization (WHO) in 2019 shows around 1.13 million people in the world have hypertension. Non-pharmacological methods of reduction are by exercise, one of which is hypertensive gymnastics. Tera gymnastics is a physical and mental exercise combined with motion. Tera gymnastics has many benefits, one of which is improving heart conditions and blood circulation and can control blood pressure. Purpose; Knowing the results of the application of tera gymnastics on blood pressure in the elderly in Sragen Wetan District. Method; This research design uses a case study method with a descriptive research method on hypertensive elderly using a spygmomanometer. Result; Blood pressure before the application of tera gymnastics in respondents was included in the category of Grade I hypertension. There were differences in the development of blood pressure in the elderly with hypertension before and after the tera gymnastics intervention became Grade I hypertension. Conclusion; There are differences in development before and after tera gymnastics in the elderly with hypertension.